Immune-related gene signature associates with immune landscape and predicts prognosis accurately in patients with skin cutaneous melanoma - Shen, Xin; Shang, Lifeng; Han, Junwei; Zhang, Yi; Niu, Wenkai; Liu, Haiwang; Shi, Hai (Frontiers in Genetics, 2023)
Skin cutaneous melanoma (SKCM) is the skin cancer that causes the highest number of deaths worldwide. There is growing evidence that the tumour immune microenvironment is associated with cancer prognosis, however, there is little research on the role of immune status in melanoma prognosis. In this study, data on patients with SKCM were downloaded from the GEO, TCGA, and GTEx databases. Genes associated with the immune pathway were screened from published papers and lncRNAs associated with them were identified. we performed immune microenvironment and functional enrichment analyses. The analysis was followed by applying univariate/multivariate Cox regression algorithms to finally identify three lncRNAs associated with the immune pathway for the construction of prognostic prediction models (CXCL10, RXRG, SCG2). The model's reliability analyses show that it was able better differentiate the prognostic value and continued existence of SKCM patient populations. At last, this study is an analysis of the immune path that leads lncRNAs in SKCM which aims to open up new pathways for SKCM treatment.